A Dictyostelium model for BPAN disease reveals a functional relationship between the WDR45/WIPI4 homolog Wdr45l and Vmp1 in the regulation of autophagy-associated PtdIns3P and ER stress. Issue 3 (4th March 2022) - Tornero-Écija, Alba; Tábara, Luis-Carlos; Bueno-Arribas, Miranda; Antón-Esteban, Laura; Navarro-Gómez, Cristina; Sánchez, Irene; Vincent, Olivier; Escalante, Ricardo
ABSTRACT: PROPPINs are conserved PtdIns3P-binding proteins required for autophagosome biogenesis that fold into a characteristic group of seven-bladed beta-propellers. Mutations in WDR45/WIPI4, a human member of this family, lead to BPAN, a rare form of neurodegeneration. We have generated mutants for the two PROPPIN proteins present in the model system Dictyostelium discoideum (Atg18 and Wdr45l) and characterized their function. Lack of Wdr45l greatly impairs autophagy, while Atg18 only causes subtle defects in the maturation of autolysosomes. The strong phenotype of the Wdr45l mutant is strikingly similar to that observed in Dictyostelium cells lacking Vmp1, an ER protein required for omegasome formation. Common phenotypes include impaired growth in axenic medium, lack of aggregation, and local enrichment of PtdIns3P as determined by the use of lipid reporters. In addition, Vmp1 and Wdr45l mutants show a chronically active response to ER stress. For both mutants, this altered PtdIns3P localization can be prevented by the additional mutation of the upstream regulator Atg1, which also leads to recovery of axenic growth and reduction of ER stress. We propose that, in addition to an autophagy defect, local autophagy-associated PtdIns3P accumulation might contribute to the pathogenesis of BPAN by disrupting ER homeostasis. The introduction of BPAN-associated mutations in Dictyostelium Wdr45l reveals the impact of pathogenic residues on the function and localization of the protein.